The impact of digitalization on social and pedagogical work development - Vdovina, Margarita; Firsov, Mikhail; Karpunina, Anastasia; Sizikova, Valeria; Bogatov, Denis (Nuances: estudos sobre Educação, 2021)
The article presents the results of an empirical study conducted by the authors according to the method of an online questionnaire survey (n = 157) in 2020. The respondents are Russian social workers. The study is aimed at identifying the specifics of the use of digital technologies in the professional activities of social workers and managers in the social sphere. The article analyses the effectiveness of the use of digital tools and highlights the problems in this activity. The authors also try to identify ways of solving these problems for the possible increase of the efficiency of digitalization in social work. The analysis of the respondents’ opinions has shown that among the main advantages are the increase in the efficiency of a labour organization (acceleration of data processing, automation of document management, online purchases and delivery) and obtaining the necessary information, including from other departments.